The role of bilirubin as a biomarker of rheumatic diseases: a systematic review and meta-analysis - Zinellu, Angelo; Mangoni, Arduino A. (Frontiers in Immunology, 2024)
The identification of novel, yet easily measurable biomarkers of inflammation and oxidative stress might assist in the diagnosis and management of patients with rheumatic diseases (RDs). We conducted a systematic review and meta-analysis of studies investigating the circulating concentrations of bilirubin, the end product of heme metabolism and a potent endogenous antioxidant with anti-inflammatory properties, in patients with RDs and healthy controls. The electronic databases PubMed, Scopus, and Web of Science were searched from inception to 31 December 2023 for relevant articles. We evaluated the risk of bias and the certainty of evidence using the Joanna Briggs Checklist and the Grades of Recommendation, Assessment, Development, and Evaluation Working Group system, respectively. In 17 eligible studies, all with low risk of bias, compared to controls, patients with RDs had significantly lower concentrations of total bilirubin (standard mean difference, SMD=-0.68, 95% CI -0.91 to -0.44, p˂0.001; I 2 =92.5%, p<0.001; low certainty of evidence), direct (conjugated) bilirubin (SMD=-0.67, 95% CI -0.92 to -0.41, p˂0.001; I 2 =81.7%, p<0.001; very low certainty of evidence), and the active antioxidant and anti-inflammatory indirect (unconjugated) form of bilirubin (SMD=-0.71, 95% CI -1.18 to -0.24, p=0.003; I 2 =95.1%, p<0.001; very low certainty of evidence). The results of the meta-analysis were stable in sensitivity analysis. In meta-regression, there were no significant associations between the SMD of total bilirubin and several clinical and demographic characteristics, including age, male to female ratio, number of participants, liver enzymes and erythrocyte sedimentation rate. In subgroup analysis, the SMD of total bilirubin was significant across a range of RDs, including rheumatoid arthritis, systemic lupus erythematosus, primary Sjögren syndrome, and myositis. Therefore, the results of our systematic review and meta-analysis suggests that the reductions in bilirubin concentrations observed in patients with RDs reflect a state of impaired antioxidant and anti-inflammatory defence due to bilirubin consumption and highlight the promising role of this endogenous product as a biomarker of RDs. (PROSPERO registration number: CRD42023500649).